Use of the Leptospira sp. ligB C-terminus coding region as a diagnostic tool of animal leptospirosis - Saraullo, Vanina Rosa; Grune Loffler, Sylvia; Florin-Christensen, Mónica; Watanabe, Olivia; Hamer, Micaela; Martinez, Mara Leila; Brihuega, Bibiana Felicitas (Elsevier, 2021)
Leptospirosis is the most widespread zoonosis worldwide, and it can cause reproductive failures in livestock, while in humans may vary from a mild fever to multi-organ failure and death. Due to this, in this study, we evaluated the usefulness of the segment encoding LigB C-terminus region, only present in pathogenic as target for a diagnostic PCR. This new PCR yielded a 100 % positivity for pathogenic Leptospira species and no cross-reactivity was found with intermediate or non-pathogenic species, or with other microorganisms, demostrating its high analytical specificity. The estimated analytical sensitivity was higher in serum samples than in blood or urine samples (6−9 × 102 lept/mL and 6−9 × 105 and 6−9 × 106 lept/mL, respectively). Multiple sequence alignment of the target region from different pathogenic Leptospira species confirmed that this gene region is highly conserved among these species, with few single nucleotide polymorphisms. The ligb-ct PCR here developed appears as a useful tool for the molecular diagnosis of leptospirosis.